A note on condition numbers for generalized inverse A T , S ( 2 ) and constrained linear systems - Liu, Gang; Lu, Shengqi; Chen, Juping; Xu, Wei (Applied mathematics and computation, 2010)
In this paper, we use the Schur decomposition to measure the sensitivity of the general inverse A T , S ( 2 ) and the constrained singular linear system Ax = b with regard to 2-norm and F-norm, rather than PQ-norm in [12], where P and Q are nonsingular matrices. The explicit forms of the condition numbers approximate the sensitivity of A T , S ( 2 ) and the constrained singular linear system pretty well. Furthermore, since Schur decomposition is well-posed, the evaluation of the sensitivity can be numerically easy and stable.